‘PRO ENFORCEMENT BIAS’ UNDER ARTICLE V OF THE NEW YORK CONVENTION IN INTERNATIONAL COMMERCIAL ARBITRATION: COMPARATIVE OVERVIEW - Junita, Fifi -, - (UI Scholars Hub, 2015)
This article explores the main features of exceptions to enforcement under Article V of the NYC, including its exhaustive and discretionary natures. It then specifically provides an overview of narrow judicial control over the grounds for refusing enforcement under the Article V of the NYC. It points out the fundamental principles of the provision in determining the enforceability of international arbitral awards. Then this article will occasionally refer to international arbitral cases in some jurisdictions, such as the United States, France and Switzerland. It is noted that courts and legislatures in those jurisdictions have moved towards pro-enforcement policy to questions of recognition and enforcement arising under Article V of the NYC. Therefore, this approach is a good signal and a promising development to promote the finality and enforeability of foreign arbitral awards in international commercial arbitration. This approach can also be a good lesson for the Indonesian judiciary system in relation to the enforcement and recognition of international arbitral awards in the future.